The Economic Analysis of the Overlooked Recurrent Low Back Pain: Three Years Retrospective Observational Study - Szyszka J; Matuska J; Szyszka BG; Walkowiak D; Skorupska E (Journal of Pain Research)
Jarosław Szyszka,1 Jakub Matuska,2,3 Bartosz Grzegorz Szyszka,4 Dariusz Walkowiak,5 Elżbieta Skorupska6 1Department of Orthopaedic Surgery, Opolskie Center of Rehabilitation, Korfantow, Poland; 2Doctoral School, Poznan University of Medical Sciences, Poznan, Poland; 3Doctoral School, Rovira I Virgili University, Reus, Spain; 4Worcestershire Acute Hospitals NHS Trust, Worcester, England; 5Department of Organisation and Management in Health Care Poznan University of Medical Sciences, Poznan, Poland; 6Department of Physiotherapy, Poznan University of Medical Sciences, Poznan, PolandCorrespondence: Elżbieta Skorupska, Department of Physiotherapy, Poznan University of Medical Sciences, ul. 28 Czerwca 1956 r. 135/147, Poznań, 61-545, Poland, Email skorupska@ump.edu.plPurpose: Recent redefinitions of pain emphasize the importance of the previously overlooked recurrent low back pain (LBP). Understanding the direct medical cost for recurrent LBP cases based on the cost per visit is crucial economically. We aimed to compare the cost per visit for LBP and recurrent LBP, including the impact of gender and type of medical service, estimating the approximate annual cost of recurrent LBP.Patients and Methods: Data on LBP categorized according to ICD-10 codes (G54, G55, M45, M46, M47, M48, M49, M51, M53, and M54) from the Polish National Health Fund (NHF) and Opolskie Rehabilitation Center (OCR) were analyzed based on the recurrent state as outlined in the new chronic pain definition.Results: In OCR, a recurrent LBP was confirmed for 22.78% of patients, of which 59.72% were female (p< 0.001). The mean value of a single procedure for recurrent LBP was 110.56 EUR, it was significantly higher for males (135.35 EUR) than for females (92.94 EUR) (p=0.008). Recurrent LBP generated a higher cost per visit for medical services than LBP (p< 0.001), except for physiotherapy. Notably, males had a higher cost per visit in inpatient admissions, while females had a significantly higher cost per visit in physiotherapy services for both LBP and recurrent LBP. Moreover, recurrent LBP generated a statistically higher cost per visit for medical services than non-recurrent cases, except for physiotherapy. The average annual cost of LBP-related medical services in Poland was € 243,861,639.Conclusion: Recurrent LBP accounts for 5% of total direct LBP costs and has a higher cost per visit than LBP, excluding physiotherapy services. Gender significantly affected per-visit costs, with males having more inpatient admissions and females utilizing more physiotherapy services for both LBP and recurrent LBP.Keywords: cost analysis, recurrent low back pain, medical services, multidisciplinary care, biopsychical model of pain, ICD-11